Financial Statement Fraud, Audit Committee and Audit Quality: Insight into Fraud Diamond Theory - Nikmah, Nikmah; Arjoen, Muhammad Robby (International Journal of Social Service and Research, 2023)
Based on the Fraud diamond theory, the study investigates whether the audit and quality committee can strengthen or weaken financial statement fraud. this study aims to prove the influence of diamond fraud on the potential for financial statement fraud and that the audit and quality committee can strengthen or weaken the effect of diamond fraud on the potential for financial statement fraud. This study sample was selected using the purposive sampling method and obtained 850 observations from 214 companies’ sector non-financial listed on Indonesia Stock Exchange from 2016-2019. Furthermore, this study uses secondary data obtained from www.idx.co.id and each company's website. Data analysis in this study using logistic regression. The result of this study indicates that variable financial stability, board change, and financial target positively affect the detection of fraudulent financial statements. In contrast, variable external pressure, ineffective monitoring, and auditor change do not affect the detection of fraudulent financial statements. As the first variable moderating in this study, the audit committee does not affect weakening the relationship between fraud diamonds and fraudulent financial statements. On the other hand, audit quality, as the second moderating variable in this study, weakens the relationship between external pressure and ineffective monitoring of fraudulent financial statements.